O passado ameaça o futuro Tocqueville e a perspectiva da democracia individualista - Magalhães, Fernando (2000)
The history of democracy, in modern times, has coincided, in general terms, with the history of American democracy. Ever since Tocqueville pointed out the irresistible strength of this form of government, Western societies have done their best to adopt it as a model. It represents, to the great majority of contemporary people, the sole type of political regime that is able to lead humanity to its fulfilment - to conquer personal freedom and equality of opportunity. However, this equalitarian development is also responsible for the negative aspects of its functioning. Democracy runs the risk of transforming itself into its own antithesis. This would jeopardize its own system in two ways: by the action of its agents and by its specific excluding individualistic content. This paper tries to show, in a concise fashion, not only Tocquevilles concern over the destinies of this form of government, but also how equality, isolated from its material content (social), can generate a kind of discrimination which makes democratic society violent and unfair.